Awareness on Oral Cancer among the community People of Baglung - Shrestha, Saphalta (NPRC Journal of Multidisciplinary Research, 2025)
Background: Oral cancer is the leading cause of death globally and affecting developing countries as well. A descriptive cross sectional study design was conducted to assess awareness on oral cancer among community people of Baglung. Methods: Study was conducted in selected hospitals in in ward no 3 of Galkot municipality, Baglung using a non-probability purposive sampling technique to select the 116 sample. Face to face interview was carried out through structured questionnaire to collect the data. The data was coded, entered into SPSS version 16, and analyzed using both descriptive and inferential statistics (Chi-square test). Results: The finding of the study revealed that 44% of the respondents were in the age group of 30-39 years with mean age of 33.59±6.62 years and more than half of respondents (56%) were females whereas majority of the respondents 33.6% were home maker. Majority of the respondents 89.7% were aware that oral cancer is not a contagious disease. The study revealed that cent percent of the respondent were aware of lump inside mouth and 47.4% were aware about a growth of non-healing mouth ulcer as a sign and symptoms of oral cancer. The study revealed that only 8.6.% of respondents had adequate awareness. Conclusion: In conclusion, most of the respondents have inadequate level of awareness on oral cancer. There is need for awareness program on oral cancer among adults in community through mass campaign and training.